Compressive Strength and Water Absorption of Sand Cement Brick that Incorporated with Construction Tiles Waste - Mat Dom, Adek Ainie; Abdul Hamid, Noor Azlina; Jamaluddin, Norwati; Thamrin, Rendy (International Journal of Sustainable Construction Engineering and Technology, 2023)
Ceramic Tiles Waste (CTW) is one of the major sources of construction and demolition (C&D). Recycling the C&D waste is one of the most effective ways to develop sustainable building elements. In this study, the CTW were used as a partial sand replacement in sand cement brick. The percentages replacement of CTW are 0%, 10%, 20%, 30%, 40% and 50% by mass of the sand with mix design ratio of 1:3 and 0.6 water cement ratio. All the bricks were curing up to 90 days. The density, compressive strength and water absorption of sand cement bricks were also determined for its mechanical and durability performance. The experimental results reveal that the optimum replacement of CTW in sand cement brick is in range of 10% to 40% that give a good performance in compressive strength. The compressive strength of sand cement bricks increases in range of 10.17% up to 30.82% for each stage of curing days from 7 days up to 90 days. Meanwhile, the percentage of water absorption of sand cement bricks at 28 days up to 90 days of curing are below 12% as per stated in ASTM C90.